0357 The lifetime risk approach to estimating the burden of occupational cancer. (23rd June 2014) - Fritschi, Lin; Carey, Renee; Peters, Susan; Reid, Alison; Driscoll, Tim; Rushton, Lesley; Glass, Deborah; Hutchings, Sally
Abstract : Objectives: The main approaches to estimating the burden of occupational cancer are attributable risk and lifetime risk. In this presentation we will explain why we used the lifetime risk approach. Method: The lifetime risk of cancer is an estimation of an individual's risk of being diagnosed with cancer during their life (without considering occupational exposures). The lifetime risk for the general population (LRGP ) is estimated by multiplying cohort person-years-at-risk (from life table data) by age-sex specific incidence rates. The excess lifetime risk of cancer in a cohort of workers exposed to the carcinogen of interest (LRexposed ) is a product of the LRGP and the excess relative risk of developing cancer associated with that exposure. LRexposed is multiplied by the prevalence of exposure to obtain the number of cancers attributable to the exposure in the general working population. Results: The lifetime risk approach estimates the number of cancers which would occur over a number of years in the future, due to exposures in a specific year. In contrast, the attributable risk approach estimates the number of cancers which would occur in a specific year due to exposures over a number of years in the past. Because we had exposure prevalence information for a specific year based on a national survey, we determined that the lifetime risk approach was more applicable in our case. Conclusions: The lifetime risk approach is an alternative method for calculating burden of disease when exposure prevalence information is available.